Depressive symptoms increase the risk of falls and injurious falls in Chinese adults aged ≥ 45 years: A 3-year cohort study - Bu, Hanli; Lu, Suqing; Wang, Linxian; Jiang, Dan; Tian, Zhenzhen; Ding, Yi; Zhuang, Qin (Frontiers in Public Health, 2022)
Background: Falls and depressive symptoms are both public health concerns in China, but the effects of depressive symptoms on falls and injurious falls have not been thoroughly investigated. Methods: This population-based prospective cohort study used data derived from adults aged ≥ 45 years acquired from the 2015 and 2018 China Health and Retirement Longitudinal Study. Data were analyzed from August 2021 to December 2021. Self-reported depressive symptoms were determined using a 10-item Center for Epidemiologic Studies Depression scale (CESD-10) with a total score range of 0 to 30. Item responses of 3–4 days or 5–7 days were deemed indicative of specific depressive symptoms. The outcome variables were self-reported accidental falls and injurious falls. Results: Of the 12,392 participants included in the study, 3671 (29.6%) had high baseline depressive symptoms (CESD-10 scores ≥ 10), 1892 (15.3%) experienced falls, and 805 (6.5%) experienced injurious falls during 2015–2018 follow-up. High depressive symptoms increased the risk of falls (odds ratio [OR] 1.34, 95% confidence interval [CI] 1.19–1.50) and injurious falls (OR 1.28, 95% CI 1.09–1.51) in a multivariable logistic regression model adjusted for major demographic, health related, and anthropometric covariates. All of the 10 specific depressive symptoms except “felt hopeless” were associated with falls, and four specific symptoms significantly increased the risk of injurious falls; “had trouble concentrating” (OR 1.32, 95% CI 1.13–1.55); “felt depressed” (OR 1.32, 95% CI 1.12–1.55); “everything was an effort” (OR 1.23, 95% CI 1.04–1.45); and “restless sleep” (OR 1.18, 95% CI 1.02–1.40). Conclusions: High depressive symptoms are significantly related to risk of falls and injurious falls. Four specific symptoms (had trouble concentrating, felt depressed, everything was an effort, and restless sleep) increase the risk of injurious falls in Chinese adults aged ≥ 45 years.